Molecular characterization of antibiotic resistant gene of Staphylococcus aureus isolated from hospitals - HUSSEIN HAMEED ABBAS; JASIM MOHAMMED SADEQ (International Journal of Pharma and Bio Sciences, 2017)
The Multiple Antibiotic Resistance of Methicillin Resistant Staphylococcus aureus (MRSA) has become a major clinical problem worldwide. With increasing incidence of resistance in microbes and decreasing rates of discovery of newer effective antibiotics, we are almost on the verge of an impending medical disaster. Microbial resistance is, therefore, a major cause of concern. It is no more a neglectable risk but a real threat to our survival on earth. Molecular methods for detection of MRSA is a potentially valuable development to reduce test time and increase sensitivity and specificity. It is most important that any method should accurately distinguish between MRSA and mixtures of methicillin-susceptible S. aureus with methicillin-resistant staphylococci present in the sample .Cost-effectiveness data are still awaited but we would anticipate a progressive introduction of this PCR-based technology into clinical practice at an early date.